Energy Effective Congestion Control for Multicast with Network Coding in Wireless Ad Hoc Network. (22nd May 2014) - Zhao, Chuanxin; Luo, Yonglong; Chen, Fulong; Zhang, Ji; Wang, Ruchuan
Abstract : In order to improve network throughput and reduce energy consumption, we propose in this paper a cross-layer optimization design that is able to achieve multicast utility maximization and energy consumption minimization. The joint optimization of congestion control and power allocation is formulated to be a nonlinear nonconvex problem. Using dual decomposition, a distributed optimization algorithm is proposed to avoid the congestion by control flow rate at the source node and eliminate the bottleneck by allocating the power at the intermediate node. Simulation results show that the cross-layer algorithm can increase network performance, reduce the energy consumption of wireless nodes and prolong the network lifetime, while keeping network throughput basically unchanged.